MODERASI ANTAR AGAMA: TELAAH GAYA KOMUNIKASI ISLAM DAN KATOLIK DI DESA KLEPU PONOROGO - Langgeng Setiyono; M. Irfan Riyadi (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2022)
Abstract : This paper aims to describe the pattern of Moderation in the village of Klepu through patterns of communication styles between Muslims and Catholics, especially during the celebration of Christmas and Eid al-Fitr. Moderation includes patterns of communication styles between religious people in Klepu village and forms of moderation in religious communication in Klepu village. The method used in this study is descriptive with a Qualitative approach. The location of this study is in Klepu village, Sooko District, Ponorogo Regency. Meanwhile, data sources are obtained from interviews, observations and documentation. The collected data were analyzed with the theory of communication style, tolerance, and moderation (tolerance). From the analysis of this study can be drawn conclusions 1). The communication style in Klepu Village from Islam and Catholicism is classified into 4 kinds, namely: a). the equalitarian style: the Traditional Islamic communication model (jam'iyah NU) with the style of equalityn. b). the controlling style and the dynamic style: a modern Islamic communiqué model (Muhammadiyah) with a Controlling style and a dynamic style with certain prerequisites. c). the structuring style: The Puritanical Islamic communication model (DDII) with the Style of Controlling is full of structural style. d). The relighuishing style and equalitarian style: a Catholic style of communication that prioritizes flexibility and equality 2). Religious moderation was formed with tolerance as a medium of communication in Klepu village in joint social activities, namely: arisan, sinoman (youth), mutual aid, and socio-religious ritual activities, namely: Slametan and birth and death events.